TICRR Contributes to Tumorigenesis Through Accelerating DNA Replication in Cancers - Yu, Qin; Pu, Shao-Yan; Wu, Huan; Chen, Xiao-Qiong; Jiang, Jian-Jun; Gu, Kang-Shuyun; He, Yong-Han; Kong, Qing-Peng (Frontiers in Oncology, 2019)
DNA replication is precisely regulated in cells and its dysregulation can trigger tumorigenesis. Here we identified that the TOPBP1 interacting checkpoint and replication regulator (TICRR) mRNA level was universally and highly expressed in 15 solid cancer types. Depletion of TICRR significantly inhibited tumor cell growth, colony formation and migration in vitro, and strikingly inhibited tumor growth in the xenograft model. We reveal that knockdown of TICRR inhibited not only the initiation but also the fork progression of DNA replication. Suppression of DNA synthesis by TICRR silencing caused DNA damage accumulation, subsequently activated the ATM/CHK2 dependent p53 signaling, and finally induced cell cycle arrest and apoptosis at least in p53-wild cancer cells. Further, we show that a higher TICRR level was associated with poorer overall survival (OS) and disease free survival (DFS) in multiple cancer types. In conclusion, our study shows that TICRR is involved in tumorigenesis by regulating DNA replication, acting as a common biomarker for cancer prognosis and could be a promising target for drug-development and cancer treatment.